Effect of using crochet octopus in reducing the pain: a randomized controlled study - SABAZ, NAGİHAN (My University, 2022)
Aims The study aimed to determine the effect of using a crochet octopus to reduce acute pain and maintain optimal physiological measurements that develops during procedural pain in neonates. Materials and methods This was a parallel design randomized controlled study. During the procedure of heel lance, experimental groups were delivered a crochet octopus 10 min before the process and let them touch the octopus during and for up to 10 min after the procedure. Control group experienced the process without any intervention. SpO(2), duration of crying of neonates and pain they experienced were evaluated. Results The study was completed with 100 (50 for the experimental group and 50 for the control group) term neonates. SpO(2) of neonates, touching the crochet octopus during and after in second minute of the process was found higher and also the duration of crying was shorter during whole the process, and the pain they experienced due to the process was lower than the control group. Conclusions Crochet octopus affected physiological measurements of the neonates positively and reduced the procedural pain as well.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); TROPİKAL TIP; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); TROPICAL MEDICINE; Farmasötik bilim; Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Yaşam Bilimleri; Pharmaceutical Science; Pediatrics; Pediatrics, Perinatology and Child Health; Life Sciences; neonate; nursing; pain; pain management; procedural pain; non-pharmacological method; NEONATAL PAIN